Multifaceted roles of transcription factors during plant embryogenesis - Yuan, Hai Ying; Kagale, Sateesh; Ferrie, Alison M. R. (Frontiers in Plant Science, 2024)
Transcription factors (TFs) are diverse groups of regulatory proteins. Through their specific binding domains, TFs bind to their target genes and regulate their expression, therefore TFs play important roles in various growth and developmental processes. Plant embryogenesis is a highly regulated and intricate process during which embryos arise from various sources and undergo development; it can be further divided into zygotic embryogenesis (ZE) and somatic embryogenesis (SE). TFs play a crucial role in the process of plant embryogenesis with a number of them acting as master regulators in both ZE and SE. In this review, we focus on the master TFs involved in embryogenesis such as BABY BOOM (BBM) from the APETALA2 / Ethylene-Responsive Factor (AP2/ERF) family, WUSCHEL and WUSCHEL-related homeobox (WOX) from the homeobox family, LEAFY COTYLEDON 2 (LEC2) from the B3 family, AGAMOUS-Like 15 (AGL15) from the MADS family and LEAFY COTYLEDON 1 (LEC1) from the Nuclear Factor Y (NF-Y) family. We aim to present the recent progress pertaining to the diverse roles these master TFs play in both ZE and SE in Arabidopsis, as well as other plant species including crops. We also discuss future perspectives in this context.